Wirtschaft, Krieg und Seelenheil Papst Martin V., Kaiser Sigismund und das Handelsverbot gegen die Hussiten in Böhmen - Kaar, Alexandra (2020)
The monograph deals with the embargo, which was imposed by the papacy and the Catholic lay powers upon all trade and commerce with the Czech Hussites between 1420 and 1436. The author explores this anti-Hussite embargo by showing how it was enforced and how the political agents involved used it as a tool of governance and propaganda. The book presents a new, holistic view of the anti-Hussite trade embargo as a complex historical phenomenon, thus contributing to the political, economic and cultural history as much as to the history of everyday life in early 15th century Central Europe.